Comparative analysis of data mining techniques for business data - Jamil, Jastini; Mohd Shaharanee, Izwan Nizal (2014)
Data mining is the process of employing one or more computer learning techniques to automatically analyze and extract knowledge from data contained within a database.Companies are using this tool to further understand their customers, to design targeted sales and marketing campaigns, to predict what product customers will buy and the frequency of purchase, and to spot trends in customer preferences that can lead to new product development.In this paper, we conduct a systematic approach to explore several of data mining techniques in business application.The experimental result reveals that all data mining techniques accomplish their goals perfectly, but each of the technique has its own characteristics and specification that demonstrate their accuracy, proficiency and preference.